Lateral violence among registered nurses working in government hospitals of UAE - Alyileili, Aishah Khameis Khalfan Obaid (2013)
Workplace violence in healthcare setting is a worldwide phenomenon. The nature of workplace violence in the nursing context is mainly a nonphysical behavior. The literature shows the consequences for the individual, either physically or emotionally, depending on the nature of the violence act itself. This research study investigates the extent of workplace violence, targeting registered nurses working in Ministry of health hospitals (MOH). The research objectives addressed a variety of aspects, such as types, prevalence, perpetrators, consequences, and management of workplace violence. For the sake of this study, a quantitative, descriptive research design, utilizing a comprehensive survey, was chosen for conducting this research study. This study included 1077 registered nurses (RN) working in six government hospitals. The study findings revealed that the perpetration of nonphysical violence acts against registered nurses is widespread, particularly that perpetrated by patients’ relatives and patients. Though the respondents know and understand the procedures of how and where to report any episode of workplace violence, but unfortunately, most of them were disappointed because no actions will be taken by the authority. All of these findings have particular implications towards the management of workplace violence as the recommendations arising from this study directed at specific areas, such as the role of management, creation of awareness, empowerment of RN nurses, and nurses’ support. Finally, this research study suggests other recommendations for further research concerning the issue of Lateral Violence.